2022
DOI: 10.1007/s10943-022-01536-2
|View full text |Cite
|
Sign up to set email alerts
|

GPs´ Personal Spirituality, Their Attitude and Spiritual Competence: A Cross-Sectional Study in German General Practices

Abstract: To understand if GPs’ spiritual competence, their personal spirituality and attitude towards enquiring about spirituality in practice interrelate, we conducted a cross-sectional survey of 30 German GPs regarding issues of SC. We found correlations between GPs’ personal spirituality, their spiritual competence and their attitudes towards SC. The ability to perceive spiritual needs of patients was the competence most strongly related to GPs’ attitude towards SC. The competence with the strongest correlation to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This diversity complicates the establishment of a universally accepted spiritual care competence and interferes with expected and delivered spiritual care. The ability to differentiate between spirituality and religion is deemed crucial [ 54 , 60 ] to understand and articulate how personal spiritual experience influences the delivery of spiritual care [ 21 , 26 , 51 , 52 , 53 , 59 , 68 , 69 ]. This skill extends to defining key concepts such as PC, religion, spirituality, and spiritual care itself, as suggested by Dezorzi et al [ 55 ], thereby enriching the professional’s capacity to provide nuanced and culturally sensitive spiritual care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity complicates the establishment of a universally accepted spiritual care competence and interferes with expected and delivered spiritual care. The ability to differentiate between spirituality and religion is deemed crucial [ 54 , 60 ] to understand and articulate how personal spiritual experience influences the delivery of spiritual care [ 21 , 26 , 51 , 52 , 53 , 59 , 68 , 69 ]. This skill extends to defining key concepts such as PC, religion, spirituality, and spiritual care itself, as suggested by Dezorzi et al [ 55 ], thereby enriching the professional’s capacity to provide nuanced and culturally sensitive spiritual care.…”
Section: Resultsmentioning
confidence: 99%
“…Mächler et al [ 69 ] emphasized the interrelationship between an individual’s spirituality and their professional conduct and their competencies in spiritual care, which significantly influences both patient outcomes and professional development [ 69 ]. This interplay demands careful consideration by healthcare administrators and PC professionals when structuring care delivery, organizing the workplace, and creating conducive environments for the practice of spiritual care [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Atheists and agnostics may be aware of their norms, values, points of view, or (non)religious/spiritual history and identity and how they influence their professional role, but they may be faced with different challenges in providing spiritual care (Magaldi-Dopman et al 2011) in comparison with their believing and practicing-prayer and/or -meditation peers. However, research shows that the personal spirituality of the health professional is critical for providing spiritual care, and this calls for further research (Mächler et al 2022). One study for example showed that, also across cultures, identifying oneself as not-or slightly-spiritual was predictive of not providing spiritual care (Bar-Sela et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Bożek et al (2020) research show that spirituality and health-related behaviors are positively related to psychological well-being, and are also mediated by health-related behaviors. There is a link between personal spirituality and spiritual competence (Mächler et al, 2022). The results of Madelo's research have found that there is a significant relationship between the spirituality of educators and the development of students' 21st-century skills…”
Section: The Effect Of Pjbfl Media On Samentioning
confidence: 99%